Gestión Turística y Desarrollo en las Comunidades Indígenas en parroquia San Juan, cantón Riobamba. - Guamán Cepeda, Brayan Stalyn (2022)
This research refreshes, updates, suggest improvements in the tourism management of indigenous communities in the province of Chimborazo, aimed at community development. The existence of numerous community organizations in this province, and the lack of knowledge of the real state in terms of community tourism management, requires the updating of tourism management models, capable of strengthening the development of these communities. Then, methodologies, tools and instruments are provided in favour of competitiveness in tourist services and their management, and in such a way, satisfy the expectations of visitors. In this investigative work, the field of study is tourism management based on community development. It is notable today, the absence of evidence of the current state of community tourism management, in addition to the lack of knowledge by the community actors in charge of tourism service and management. Variables that limit performance, such as, degree of community organization, state of community motivation to offer services, a vision of strategic planning of tourism management, organizational control, negatively influence the performance of tourism management. Then, a knowledge gap related to the state of community tourism management and suggestions to develop the management is filled. The objective achieved in this research has been to determine the relationship between tourism management and development in indigenous tourism communities in the San Juan parish, Chimborazo province. In addition, is determined the relationship between planning, the organization, the direction and the control for the development of the indigenous tourist communities of the San Juan parish of the Chimborazo province is determined. The hypothesis is validated by determining the relationship between tourism management, it is possible to improve development in the tourist communities of the San Juan Parish, Chimborazo province.